THE VARIATION OF CALCIUM, MAGNESIUM, SODIUM, POTASSIUM AND BICARBO NATE CONCENTRATION, pH AND CONDUCTIVITY IN GROUNDWATER OF KARACHI REGION (Biological Sciences - PJSIR, 2002)
Groundwater in Karachi is influenced mainly by the evaporation / crystallization process as expressed  by  the  Na/  (Na+Ca) weight concentration ratio. The high coefficient of determined between conductivity and total dissolved ions concentration in meq·1 revealed  that major ions affect the conductivity of groundwater. It was also found that groundwa  ter quality with respect to cations is not significantly influenced by geology, particularly in the Urban  area of the  city, where the 90% of the population resides . The relationship between conductivity and  bicarbonate  concentration  shows  that  supersaturation  of groundwater  with  carbon  dioxide  is responsible  for general  depression  of  pH.